Temporal interbank market network: a multi-layered network approach - Quek, Jing Ting (Nanyang Technological University, 2022)
Despite the interbank market playing a pivotal role in facilitating liquidity provision among banks, it might also result in possible pathways of contagion, which might, in turn, lead to the consequent failing of banks and the system as a whole. In this paper, we model cascades of collapses in interbank lending networks using simulations and study the extent and length of contagion effects. We found that network stability depends on various factors such as the network structure, the initial network coherence and the type of bank experiencing the initial shock. To examine the disentangled effects of individual types of interconnections in the interbank market, multi-layer network analysis was conducted, with the results showing the significance of interactions between network layers. These findings have important policy implications, an example is it may be worthwhile to monitor the changes in measures (network structure, choice of node to default, network incoherence) of interbank network stability.